Antimicrobial Resistance Patterns of Uropathogenic Escherichia Coli in Women: A Cross-Sectional Study Kirkuk - Ahmed, Inas Thamer (Central Asian Journal of Medical and Natural Science, 2025)
Urinary tract infections (UTIs) are among the most common bacterial infections in women, primarily caused by Uropathogenic Escherichia coli (UPEC). The increasing emergence of Antimicrobial Resistance (AMR) globally limits the effectiveness of commonly used antibiotics and complicates empirical therapy. This cross-sectional study included 100 urine samples collected from female patients with suspected UTIs in Kirkuk, Iraq. All samples were cultured and identified using the VITEK 2 Compact system (bioMérieux) according to CLSI guidelines. Fifteen samples (15% of total samples) yielded significant bacteriuria and were confirmed as E. coli, while the remaining samples showed either no bacterial growth or growth of non-target organisms. Antimicrobial susceptibility testing revealed high resistance rates (over 50%) to commonly prescribed oral antibiotics, including Amoxicillin (53.3\%) and Cefalexin (53.3\%). Moderate resistance was observed for Ampicillin/Sulbactam (40.0\%), Ciprofloxacin (33.3\%), and Trimethoprim–Sulfamethoxazole (33.3\% ). Lower resistance levels were recorded for most cephalosporins and \beta-lactam/\beta-lactamase inhibitor combinations. Crucially, all isolates (15/15) remained 100\% susceptible to Amikacin, Tigecycline, Imipenem, and Meropenem. These findings highlight a significant and concerning shift in the resistance pattern among UPEC isolates in Kirkuk women. While common first-line oral treatments show limited effectiveness, Carbapenems, Amikacin, and Tigecycline remain reliable options for complicated cases. Continuous local surveillance is essential to guide updated empirical treatment protocols and mitigate the spread of multi-drug resistant strains.